Estudo da adsorção do antibiótico sulfanilamida em esmectita modificada com Na - Massariol, Polyana Silvério (2019)
The indiscriminate disposal of pharmaceutical products, as sulfanilamide antibiotic, contaminates the environment and alter the water quality. Conventional methods of removal of contaminants are expensive and present reduced efficiency by the conventional treatment methods. The adsorption is more effective for the removal of pollutants, easy operation and minimizes the amount of toxic substances in the effluents. The use of adsorbent materials, accessible and low cost, is a promising method for the adsorption of organic compounds. The potential of smectite clay was investigated in sulfanilamide adsorption in aqueous solutions by batch analysis using physical and chemical modifications in the clay in order to increase the removal capacity. The clay in natura, the clay with thermal treatment, the clay rinsed with ultrapure water, the clay rinsed with HCl solution and with NaCl solution, were investigated as adsorbent for removal of sulphanilamide (SAA). The best conditions for SAA removal was in solution at pH 4 with the clay treated at 200 °C, which fitted to pseudo first order kinetics process, and in solution at pH 8 with the clay treated with NaCl, adjusting to a pseudo second order kinetics process. The latter was chosen the optimal process condition. The SAA adsorption was described by the Langmuir isotherm by using the nonlinear method. The maximum amount of SAA adsorbed by clay was near to the experimental value (Qe at 79,79 mg g-1 at 55 °C). The temperature showed a great influence on the removal of SAA by the clay and the adsorption process was characterized as spontaneous for all temperatures studied (25, 35, 45, and 55 °C). The adsorbent material was characterized, and the X-ray diffraction allowed to identify the crystalline phases characteristic of the smectite, with structural changes according to the applied treatments, including the variation of the distance between lamellas due to the intercalation of the sodium ion. Elemental analysis, performed by EDS, showed the presence of silicon, oxygen, potassium and aluminum as the main elements of the clay structure, which are characteristic of smectite. The adsorbent showed morphology with high porosity and sodium was only identified in Na modified clay. Sodium modified clay has the potential to be used as a low cost alternative adsorbent for the treatment of effluent and waters containing the emerging sulphanilamide contaminant.